Calculation of lightning surges on the high voltage lines. Case of 220 kV line: Ngo -Brazzaville in Congo - Gomba, Rodolphe; Omboua, Alphonse (International Journal of Engineering and Technology, 2017)
The importance of line Ngo-Brazzaville (220 kV, 207 km) requires operators to avoid cuts that can increase the risk of instability. We see it is quite rare that a storm that occurs in areas crossed by this line will not cause triggering. Note that due to lightning discharges are the main causes of unscheduled outages of Congo's power lines; we ignore this during the peak values of voltage wave forms that result. In regions with high level keraunic like Congo, reducing insulation failures due to lightning is a concern in the management of overheads lines. This article clarifies the peak values of the voltages that can be achieved on the network in order to build the operators as to the precautions on the insulation coordination of protective equipment related to lightning. For these calculations surge of atmospheric origin (case of lightning), we considered the bi-exponential function and Heidler function for modeling the wave of the lightning current. This methodology led us to specially treat the effects of direct lightning strikes that constitute the worst case because they generate most destructive shock wave that indirect lightning strikes.
Keywords: Voltage; Lightning; Power Lines; Congo.